2022
DOI: 10.1002/jia2.25867
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of HIV pre‐exposure prophylaxis counselling among non‐Hispanic Black youth diagnosed with bacterial sexually transmitted infections in the United States, 2014–2019

Abstract: Introduction Youth account for a disproportionate number of new HIV infections; however, pre‐exposure prophylaxis (PrEP) use is limited. We evaluated PrEP counselling rates among non‐Hispanic Black youth in the United States after a bacterial sexually transmitted infection (STI) diagnosis. Methods We conducted a retrospective cohort study of Black youth receiving care at two academically affiliated clinics in Philadelphia between June 2014 and June 2019. We compared PrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Almost all had heard about PrEP prior to the study and over one-third self-reported prescribing PrEP. Providers rated the potential use of EHRbased CDS tools to improve HIV testing and PrEP delivery as acceptable (median score 5, IQR [4][5]) and appropriate (5, IQR [4][5]). However, feasibility ratings were slightly lower (4, IQR [3.75-4.75]), with 26% of participants disagreeing that implementation would be "easy to do."…”
Section: Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all had heard about PrEP prior to the study and over one-third self-reported prescribing PrEP. Providers rated the potential use of EHRbased CDS tools to improve HIV testing and PrEP delivery as acceptable (median score 5, IQR [4][5]) and appropriate (5, IQR [4][5]). However, feasibility ratings were slightly lower (4, IQR [3.75-4.75]), with 26% of participants disagreeing that implementation would be "easy to do."…”
Section: Quantitative Analysismentioning
confidence: 99%
“…1,2 Previous analyses have identi ed low HIV testing rates both relative to the overall prevalence of sexual activity and sexually transmitted infections (STI) in adolescents. 3,4 Despite high e cacy, PrEP delivery and counseling rates have also remained low, 2,5,6 even with Centers for Disease Control and Prevention (CDC) guidelines now recommending that all sexually active adolescents should be informed about PrEP. 7 Pediatric primary care, where most adolescents receive their routine care, is an ideal setting for HIV testing and PrEP delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Those with a recent bacterial STI (eg, gonorrhea or syphilis) are at increased likelihood of acquiring HIV and are eligible for PrEP, though HIV screening or PrEP prescribing does not often occur. 11,15,16 The overlap of the HIV and STI epidemics is an important aspect of the public health response. Addressing increasing rates of STIs should be concurrently considered as part of HIV prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have identified low HIV testing rates both relative to the overall prevalence of sexual activity and sexually transmitted infections (STI) in adolescents [ 3 , 4 ]. Despite high efficacy, PrEP delivery and counseling rates also remain low, with only 16% of youth ages 16–24 with PrEP indications receiving prescriptions [ 2 , 5 – 7 ] despite Centers for Disease Control and Prevention (CDC) guidelines now recommending all sexually active adolescents should be informed about PrEP [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data demonstrate that 10% of cisgender females with PrEP indications have been prescribed PrEP compared to 28% of cisgender males [ 25 ]. These inequities may be further magnified in adolescents, with a recent study of adolescents with STIs finding that male sex at birth patients were 26 times more likely than female sex at birth patients to receive PrEP counseling [ 5 ]. Within the pediatric primary care setting, given overall low rates of testing, there is thus a critical need for guideline-based HIV prevention service delivery to youth across sexes, sexual orientations, and gender identities.…”
Section: Introductionmentioning
confidence: 99%